Obesitas Anak di Masa Pandemi Covid-19 - OLIVIA HERLIANI (Universitas Hang Tuah, 2021)
Background: The incidence of obesity is increasing from year to year throughout the world, both in adults and children. The risk of obesity in children is getting bigger with a pandemic situation that requires children to receive distance education, limit interactions and decrease physical activity. Obesity needs special attention because it is related to clinical manifestations and prognosis of COVID-19. Objective: To raise awareness of the health risks faced by children during the COVID-19 pandemic, especially the risk of obesity. Provides an explanation of how obesity affects the clinical manifestations and prognosis of SARS-CoV-2 infection. Triggering to take preventive steps to prevent obesity and SARS-CoV-2 infection in children, as well as special attention to the management of COVID-19 patients with obesity Method: Collecting various related articles published, especially since March 2020, tracing the latest incidence rates, as well as guidelines / policies issued by health organizations related to this issue. Results: The COVID-19 pandemic increases the risk of obesity in children due to lifestyle changes, especially those related to physical activity and diet. Obesity and the nutritional condition (digestive system) of children affect the respiratory system and immune system, thus affecting susceptibility and increasing the risk of complications of COVID-19. Guidelines for the management of obesity and COVID-19 in children are available, as well as guidelines for primary, secondary and tertiary preventive measures. Conclusion: The incidence of COVID-19 in children is lower than that of adults, however the risk of health problems for children during the COVID-19 pandemic must still be considered. One of them is the occurrence of obesity which can affect endurance and increase the risk of complications of COVID-19. Preventive action, which takes precedence over curative action, requires the participation of parents, family, school and the surrounding environment. In addition, special attention needs to be paid to the management of COVID-19 patients with obesity.